Collaborative community-based governance in a transboundary wetland system in the Ecuadorian Andes - Iñiguez Gallardo, M. (2017)
International mountain conservation paradigms have shifted in the past 30 years from establishment of centrally governed protected areas that exclude communities, to collaborative and community-based conservation stewardship with communities that depend on resources for their livelihoods. The Convention on Wetlands of International Importance (Ramsar Convention) embodies this collaborative paradigm by suggesting that people and local governments can be collective stewards for the wise use of wetlands on which they depend for water resources and livelihoods. Although collaborative approaches are increasingly recommended to govern large and complex mountain waterscapes across multiple jurisdictions, recent international case study comparisons highlight the site-specific nature of institutional design and the effect that changing social relations and overlapping or conflicting rights and boundaries have on promised collaborative outcomes. This article illustrates the usefulness of a recently developed community-based natural resource management comparative framework for assessing the feasibility of collaboratively governing a proposed Ramsar wetland in the Southern Andes of Ecuador across multiple communities and jurisdictional boundaries. By using data from a rapid ethnographic assessment, US and Ecuadorian students and faculty found local and institutional support for wetland protection. The framework s preconditions were useful in identifying conflicts among and within communities, and among agency rules and resources; these conflicts could limit the feasibility of community-based and collaborative management unless coordination authority is clarified, especially at the proposed transboundary scale. This study showed that increasing attention to land tenure conflicts and institutional frameworks is needed for any collaborative governance design to be sustainable, which confirms political ecology findings.